Need help ! Will reward brainliest to the correct answer ! See posted picture above for question !
![Need help Will reward brainliest to the correct answer See posted picture above for question class=](https://us-static.z-dn.net/files/df1/5aaf17b63ddec17f2e37d00ab4e2af6f.png)
Hello there,
You merely have to just this formula and substitute the letters by the values.
[tex] \sqrt{(}x_{B}-x_{A})^2 +(y_{B}-y_{A})^2 }[/tex]
= [tex] \sqrt{((2-(-3))^2 + (-3-4)^2}[/tex]
= [tex] \sqrt{25+49}[/tex]
=[tex] \sqrt{74}[/tex]
It's about 8.6.
Hopes this helps !
Photon